Influence of Celebrity Endorsement on Consumer Buying Behaviour of Youth with Respect to Mobile Telecommunication Service Providers - Abdin, Shahnawaz; Mullick, N. H. (Journal of Commerce and Trade, 2017)
Over the years, celebrities are being increasingly used for delivering services other than performing their actual role as either an actor or sportsperson, such as endorsements. Despite the cost and the risks involved with this technique of advertising, it is being used quite extensively in contemporary times. Celebrity endorsement has nowadays become a penetrating element in advertising and communication management. India as a country is known for loving its stars. The youth population is huge in India. Indians idolize actors and cricketers. The advertisers see this as an opportunity to expand their operations and promote their product. The present research paper focuses on examining the perception of young Indian consumers about the celebrity endorsement process and the subsequent impact on their purchase decision. The research paper tries to address the topic with a literature review which provides an insight into the research done by the previous authors followed by the research method adopted to achieve the objectives of this study. A structured interview questionnaire approach has been adopted to investigate the impact of celebrity endorsement on buying behavior of youth with respect to mobile telecommunication service providers. Some of the findings derived from analyzing the collected data revealed some interesting facts which have been summarized in the conclusion. The research paper tries to address the academic as well as the managerial perspective on buying behavior of youth.